BUILDING STRONG CHARACTER AMONG MOSLEM ADOLESCENTS THROUGH DIDIKAN SUBUH AND TAPAK SUCI MARTIAL ARTS PRACTICES - Nasrullah Nasrullah; Muhammad Azhar; Nurul Satria Abdi; Kiki Kurniawan; Aqil Syahru Akram (Universitas Muhammadiyah Tapanuli Selatan, 2023)
One of the functions of the mosque that Al-Muqorrobin Islamic Center Mosque wants to play, apart from being a comfortable place for congregational prayers, is as a place for the formation of the young generation of Muslims who are strong in character. However, so far, this function is still not optimal, while the exciting activities of Youth Mosques to prosper the mosque and form the mentality and awareness of defending the country among its members are still very minimal. For this reason, this community partnership program offers two sustainable activities to address the problem of youth mosques as the program partner, namely: 1. The Subuh Education (Didikan Subuh) activities after the Fajr Prayer in the congregation every Sunday morning; 2. The practice of Tapak Suci self-defense martial art is carried out after Didikan from 6 to 8 am. The methods used in these activities are lectures, dialogue, demonstrations, and exercises led by a professional martial arts trainer. The results of the pre-test and post-test assessments of the Didikan Subuh participants showed that there had been a significant increase in the participants' religious and national insights and knowledge from an average of 32.6% in the pre-test to 64% in the post-test. While the results of routine Tapak Suci martial arts training since February 5, 2023, have produced 2 champions at the Tapak Suci Inter Kindergarten and Elementary Championships throughout the Province of Yogyakarta Special Region (MuhiMinggir Cup Competition) which held on 12-14 May 2023.